Investigating Iraqi EFL Learners’ Understanding of Using Paralinguistic Features in Obama’s Presidential Election Campaign: A Socio-phonetic Analysis - Abdullah Murdas, Saad; Mohamed Jaber Alzaghir, Alaa; Malik Mnaathar, Inas (International Journal of Psychosocial Rehabilitation, 2020)
The language of politicians, particularly when they are speaking in public, is an interesting mixture of old and new for persuasive ends. It shows much of the ritual phraseology and consciousness of precedent associated with religion or law, and it makes use of many of the rhetorical and dramatic techniques linked to advertising or the media. In order to create a successful communication, a politician has to express attitudes and emotions that are mutually known to the participants in a particular context. In which paralinguistic strategies play a major role in persuading audiences. Hence, the present study sheds light on the use of paralinguistic strategies by politicians (i.e., Obama’s presidential election race (2008)) with reference to Iraqi EFL learners understanding of pace, pitch, intensity, and pause. Methodologically, the speech was divided into six units and then delivered to the investigated students. The instrument of the study is monitoring and tape recording In terms of the results, the study found that in election rise, meaning is not essentially inherent in a word or expression, but it is given to the words and expressions by a shared understanding of a linguistic community, and paralinguistic cues play a major role in attributing some meaning to them. Statistically, only 40% of the investigated subjects understood and recognized the use of paralinguistic strategies in political discourse for persuasive ends. (see appendices.)